procedure for registration of charges in Nigeria- need for urgent reforms (2014)
The use of arbitration in commercial transactions is a vital and important aspect of every commercial agreement. This is due to the advantages of arbitration over the regular court adjudicatory process. The problem is no matter how good and impeccable the arbitral process is the law still requires that arbitral award be recognized for enforcement by the court. This paper assessed the procedure for the enforcement of arbitral domestic awards in Nigerian High Courts, examined the different forms as provided in the rules, particularly the use of Motion on Notice and Originating Summons for enforcement of arbitral award, whether these procedural forms of application are adapted or suitable for enforcement of arbitral awards or whether there should be a more flexible mode of enforcing an award and concluded that the procedures are not adequate, and totally at variance with current international standards. The paper also makes recommendation for reforms.